Submarino Based on a Novel by Jonas T. Bengtsson - Vinterberg, Thomas; Bruus Christensen, Charlotte; Cedergren, Jakob; Plaugborg, Peter; Rose, Morten (Entertainment One, 2011)
After surviving a childhood plagued by violence, two estranged brothers live haunted lives. Nick, a hardened criminal recently released from prison, spends his days in a shelter and his nights drinking excessively, while Ivan, a single father, cares for his young son while harboring his own dark secrets. Both must find a way to reconnect and fight for their future - before it's too late. [Cover]